Molecular cloning and functional studies of silicon-responsive serine-rich protein transcripts from mangrove plant, rhizophora apiculata (Blume) - Sahebi, Mahbod (2014)
Silicon (Si) is one of the most plentiful elements found in the soil. Silicon plays an important role in decreasing susceptibility of plants against variety of different biotic and abiotic stresses. Mangrove plant (Rhizophora apiculata) is able to accumulate, and process Si to generate biosilica. Therefore, it would be a beneficial source for genetic manipulation of susceptible plants in the stress conditions. The objectives of the study were (i) to identify and characterize of a Si responsive gene in mangrove,(ii) to analyze the expression levels of a gene encoding serine-rich protein, and (iii) Functional studies of serine-rich protein in Arabidopsis thaliana. Three different methods and RNeasy plant mini kit were used to extract nucleic acids. The Suppression Subtractive Hybridization (SSH) technique was used to remove transcripts from proteins which were not involved in Si accumulation. Specific primer was designed to get full-length CDS of serine-rich protein. Semi-quantitative RT-PCR and real-time PCR were performed to examine its expression level under the control and treatment conditions. The Gateway Technology was used to construct entry and the expression vectors. Transformation of Arabidopsis thaliana with serine-rich protein gene was performed using Agrobacterium-mediated transformation by the floral-dip method. Energy-dispersive X-ray spectroscopy and high performance liquid chromatography were used to measure the quantity of Si and serine amino acid, respectively. Modified CTAB and SDS were quick and reliable methods for isolation of total RNA from the roots and leaves of mangrove, respectively. Of the sequences obtained from cDNA library, four were 97% similar to serine-rich protein gene of groundnut(Arachis hypogaea). Full-length of the serine-rich protein cDNA obtained through amplification of the cDNA template using specific primers. The expression levels of serine-rich protein transcript were generally higher in the Si treated mangrove plants than untreated plants. The amount of serine amino acid of transgenic Arabidopsis has increased significantly from 1.02 mg g-1 in wild-type plants to 37.76 mg g-1. In addition, concentration of Si in the leaves and roots of transgenic plant was significantly higher than that in the wild type (P<0.01). This study successfully determined the Si responsive transcript related to serine-rich protein in mangrove plant (R. apiculata).